A design-oriented STEM activity for students' using and improving their engineering skills: the balance model with 3D printer. (2nd April 2020) - Şen, Ceylan; Ay, Zeynep Sonay; Kiray, Seyit Ahmet
Abstract: This study involves the development and implementation of a STEM activity containing 3 D printer technology, which is commonly used in STEM education. Out of school STEM courses were organized with seven middle school students studying in the 7th grade and the activities in the course were carried out with a 3D printer. One of the activities in the course is the Balance model. The study reveals the skills students used in the Balance Model activity, which is a 3D STEM activity. The students' engineering skills were effective through the STEM activity, and they actively used skills such as planning, designing, explaining the design process, creating a realistic product, and testing and evaluating product performance. In addition, it was concluded that the students use their academic and technical skills effectively. The study presents in detail the preparation and implementation process of this activity, which we think may help educators uncover and improve students' engineering skills.